Klasik Arap edebiyatında şiir eleştirisi : İbn Sellâm el-Cumahî örneği - Araz, İsmail (My University, 2024)
İbn Sellâm el-Cumahî (ö. 231/ 846 [?]), klasik dönem sözlü ve yazılı şiir eleştirisi geleneğini temsil eden önemli bir eleştirmendir. Sözlü geleneğin kaynaklarından Ebû Ubeyde ve Asmaî gibi birçok şiir eleştirmeninden faydalanmış, aynı zamanda muhaddis ve tarihçilerin telif anlayışını örnek almıştır. İbn Sellâm’ın şair ve şiirleri değerlendirirken yalnızca şiir eleştirmenleriyle sınırlı kalmamasının sebebi, müstakil bir şiir eleştirisi disiplini oluşturmak istemesidir. O, kendisinden önce fahl ve tabaka kavramları etrafında şekillenen eleştiri anlayışını ileriye taşıyarak şiir eleştirisini sınır, kural ve uzmanları belirlenmiş bir çalışma sahasına dönüştürmeyi amaçlamıştır. Çalışmada İbn Sellâm’ın hedeflediği ancak kısmen hayata geçirebildiği şiir eleştirisi projesi ele alınmıştır. Tabakât fikri ekseninde şekillenen mezkûr projenin kaynaklarının tespit edilebilmesi için şiir eleştirisinin İbn Sellâm öncesi gelişimine temas edilmiştir. Bu şekilde İbn Sellâm’ın kendisinden önceki sözlü ve yazılı gelenekten ne ölçüde beslendiği, eserinde bu geleneğe ne derece sadık kaldığı, özgün bir eleştiri paradigması geliştirip geliştiremediği tartışılmıştır. Mezkûr meseleler üzerinden İbn Sellâm’ın şiir mefhumunu tanımlama girişimi, şairleri hangi ölçütlere göre sınıflandırdığı ve müstakil bir şiir eleştirisi disiplini oluşturma hedefinde ne kadar başarılı olduğu incelenmiştir. Sistematik şiir eleştirisinin 4./ 10 yüzyılda başladığı şeklindeki genel kanaatin aksine, 3./ 9. yüzyıla dayandığını ortaya koymayı amaçlayan bu çalışmada metinleri anlama ve anlamlandırmayı öne çıkaran nitel araştırma yöntemi benimsenmiştir.

This study focuses on the evaluation of classical period’s poets and poems through the specific work of Ibn Sallam al-Jumahi (d. 231/ 846 [?]), Ṭabaqāt fuḥūl al-shuʿarā. The critique of poets and poetry, carried out orally from the pre-Islamic era to the late Umayyad period, transitioned into a written stage alongside literary activities. The main subject of the study, Ibn Sallam, a prominent poetry critic from the 3rd/ 9th century, stands out for representing both the oral and written traditions of poetry criticism. Drawing from sources in the oral tradition, including many poetry critics like Abu Ubaydah, and Asma'i, he also emulated the writing approach of hadith scholars and historians. Ibn Sallam, while evaluating poets and poems, not limiting himself to poetry critics due to he aimed to establish an independent discipline of poetry. He aimed to transform poetry criticism into a field of study with defined boundaries, rules and experts by carrying forward the understanding of criticism that was shaped around the concepts of faḥl and ṭabaqa before him. This study examines Ibn Sallam's partially realized project of poet and poetry criticism. In order to determine the sources of the aforementioned project, which was shaped around the idea of tabaqat, the development of poet-poetry criticism before Ibn Sellam was touched upon. Through this analysis, it has been discussed how much Ibn Sellam was nourished by the oral and written tradition before him, to what extent he remained loyal to this tradition in his work, and whether he was able to develop an original critical paradigm. By the topics in question, Ibn Sallam's attempt to define the concept of poetry, the criteria by which he classified poets, and how successful he was in his goal of an independent poetry criticism were examined. Contrary to the general belief, this study aims to demonstrate that the beginning of systematic poetry criticism dates back to the 3rd/ 9th century, a qualitative research method that emphasizes research and understanding was adopted. In addition, the inductive approach was used, which allows examining many data from the specific to the general, from the particular to the universal. In this way, the fundamental dynamics of Ibn Sallam's poetry criticism, which requires expertise and scientific experience, are explained.
Poetry criticism in classical arabic literature : The example of Ibn Sallām al-Jumahī
Keywords: Arabic poetry; Arap Dili ve Edebiyatı; Arap şiiri; Classical Arabic Poetry Criticism; Faḥl; Fahl Arabic language and Literature; Ibn Sallâm; İbn Sellâm; Klasik Arap Şiir Eleştirisi; Tabakât; Tabaqât